Development of low cost 3D scanner (LC3S) using Matlab and FPGA / Abdul Rais Abdul Rahim ...[et al.] - Abdul Rahman, Abdul Rais; Abdol Rahman, Mohd Adli; Ramli, Muhammad Azizi; Saparon, Azilah (UiTM Press, 2018)
Nowadays, three dimensional (3D) scanners are getting more popular with the advancement and development in technology. The 3D scanner devices inspect the object and collect ata on its shape and its appearance. The collected data is used to produce 3D models in digital format which is useful in several applications usch as in the medical field and archival purposes. The 3D model is employed to produce a CAD drawing of body part such as bones and teeth or reproduce object using rapid prototyping and milling techniques, There are several numbers of technologies used in 3D scanners either they are contact or noncontact 3D scanners but every technology has its own advances, limitations and costs. Today, there is a need for low cost 3D scanner in the market that allows user to scan an object and print it using 3D printer. So, a low cost 3D scanner is designed to produce accurate and detailed 3D model data at minimum cost for any users. Triangulation algorithm is applied and a software for scanning and improving the image is developed using MATLAB. The software is actually based on DAVID Laser scanner software. The field-programmable gate array(FPGA) Cyclone IV is used as a microcontroller to control the speed of motors and to display scanned image using Terasic Multi-Touch LCD(MTL) in the system. Two systes are developed which one is based on David Laser Scanner software with motorized laser holder and turntable while the other scanner system is developed using MATLAB application software with only one controlled servo motor. The 3D scanned image can be seen on MTL using one or multi-touch gestures.